Sintering Behavior of Molybdenite Concentrate During Oxidation Roasting Process in Air Atmosphere: Influences of Roasting Temperature and K Content - Jiangang Liu; Lu Wang; Guohuan Wu (Molecules)
Sintering is a common phenomenon, which often takes place during the oxidation roasting process of molybdenite concentrate in multiple-hearth furnaces. The occurrence of sintering phenomena has detrimental effects on the product quality and the service life of the furnace. In this work, the influence of two key factors (roasting temperature and K content) on the sintering behavior is investigated using molybdenite concentrate as the raw material. Different technologies such as XRD, FESEM-EDS, and phase diagrams are adopted to analyze the experimental data. The results show that the higher the roasting temperature is, the greater the mass loss and the more serious the sintering degree will be. The results also show that with the increase in K content, the mass loss of the raw material is first increased and then decreased, while its sintering degree is still gradually increased. The sintering products obtained during the oxidation roasting process are often tightly combined with the bottom of the used crucible with a smooth and dense surface structure, while their internal microstructures are very complicated, which not only includes numerous MoO3 species, but also unoxidized MoS2, Mo sub-oxide, SiO2, and a variety of molybdates. Among them, both MoO3 and molybdates can be easily dissolved into the ammonia solution, leading to a residue mainly composed of SiO2 and CaMoO4. This study also finds that the sintering phenomenon is caused by the increase in local temperature and the formation of various low-melting-point eutectics. It is suggested that decreasing the roasting temperature and K content, especially the K content, are effective methods for reducing the sintering degree of molybdenite concentrate during the oxidation roasting process.